THEORI ASSOSIASI DAN REDUNDANSI DALAM KOMUNIKASI - Kertopati, Ton (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2005)
The role of human communication, both oral and written is crucialI to the success of personal and corporate or institutional goals.Although the process of human communicationis essentially the same; theoretically in a multitude setting, we can see the basic process and fundamental principles and adapt them to the setting. We know that there is a great ideal of noise around us and most of it is aimed at some sort of communication. Communication is the creating of meaning through the use of signal and symbols.To understand communication, we need to appreciate the complexityof the process, for it is always dynamic